Perancangan Logo Sebagai Brand Identity Nasi Liwet Mak’e - Juliansyah, Muhammad Egi; Kharisma, Vidya (STIKOM Tunas Bangsa Pematangsiantar, 2025)
Nasi Liwet Mak'E is an MSME that serves Sundanese liwet rice dishes, founded in 2021 at Villa Mutiara Gading 2 Housing. The main focus of this business is still on production and does not yet have a clear branding strategy, as can be seen from the absence of a logo as the main identity. MSMEs need to do branding so that their business can grow big and have competitiveness. To overcome this, the Nasi Liwet Mak'E logo design process followed Alina Wheeler's procedural steps, which consisted of five steps, namely Conducting Research, Clarifying Strategy, Designing Identity, Creating Touchpoints, Managing Assets. The process begins with conducting interviews, observations and document reviews, as well as SWOT analysis. Next, the logo design concept began to be developed, which included typography and color selection, guided by the moodboard resulting from previous mindmapping. Touchpoints were then identified to improve the customer's visual experience, taking into account the internal and external needs of Nasi Liwet Mak'E MSMEs. Finally, the graphic standards manual includes guidelines for the use of logos, supporting graphics, and how to use them in various visual communication media.